Evaluation of Bedtime Basics for Babies: A National Crib Distribution Program to Reduce the Risk of Sleep-Related Sudden Infant Deaths - Hauck, Fern R. (J Community Health, 2015)
Rates of sleep-related infant deaths have remained stagnant in recent years. Although most parents are aware of safe sleep recommendations, barriers to adherence, including lack of access to a safe crib, remain. The objective of this study was to describe parental knowledge and practices regarding infant sleep position, bedsharing, pacifier use, and feeding practices before and after receipt of a free crib and safe sleep education. Bedtime Basics for Babies (BBB) enrolled high-risk families in Washington, Indiana, and Washington, DC and provided them with cribs and safe sleep education. Parents completed surveys before (“prenatal” and “postnatal”) and 1–3 months after crib receipt (“follow-up”). Descriptive and bivariate analyses were completed. 3,303 prenatal, 1,483 postnatal, and 1,729 follow-up surveys were collected. Parental knowledge of recommended infant sleep position improved from 76 % (prenatal) and 77 % (postnatal) to 94 % after crib receipt (p < 0.001). Intended use of supine positioning increased from 84 % (prenatal) and 80 % (postnatal) to 87 % after the intervention (p < 0.001). Although only 8 % of parents intended to bedshare when asked prenatally, 38 % of parents receiving the crib after the infant’s birth reported that they had bedshared the night before. This decreased to 16 % after the intervention. Ninety percent reported that the baby slept in a crib after the intervention, compared with 51 % postnatally (p < 0.01). BBB was successful in changing knowledge and practices in the majority of high-risk participants with regards to placing the infant supine in a crib for sleep. Crib distribution and safe sleep education positively influence knowledge and practices about safe sleep.